Komunikasi Rasulullah dalam Rumah Tangga - Resna Wahyuni; Ferry Darmawan (Bandung Conference Series: Communication Management, 2024)
Abstract. In the household, a lack of good communication is one of the triggers for problems. In this research, the author will discuss in more depth the discourse in the hadith of the Prophet as contained in the book "Agungnya Taman Cinta Sang Rasul". The research aims to develop the text of the hadith regarding communication with wives, and how to deal with a wife's jealousy, especially in polygamous families. The research method used is descriptive qualitative with discourse analysis by Teun A. van Dijk. The subject of the research is the hadith in the book "Agungnya Taman Cinta Sang Rasul", the object of the research is the conversation contained in the hadith. Data collection techniques were carried out using text observation, interviews and literature review. As a result, in terms of text, the main topic is about the journey of the Prophet and several of his wives and friends. It describes Aisyah's jealousy towards Shafiyyah, as well as Rasulullah's response, who understood Aisyah's condition patiently and explained it with great affection. The form of sentences in this discourse is inductive (the Prophet explained about jealousy at the end), and the text contains a coherent meaning (cause and effect relationship) with each other. Some pronouns contain deep meaning and can influence the atmosphere of communication. Using formal contextual language (telling stories related to the Sunnah of the Prophet which is a scientific story that is used as a reference). At the end of the hadith text, the Prophet used figurative sentences so that they had literary value and were full of meaning. In terms of social cognition, Aisyah felt that Rasulullah put Shafiyyah first, so jealousy emerged. From a social analysis perspective, some polygamous families still have not implemented the communication exemplified by Rasulullah. Abstrak. Dalam rumah tangga, kurang baiknya komunikasi menjadi salah satu pemicu permasalahan. Pada penelitian ini penulis akan membahas lebih dalam mengenai wacana dalam hadits Rasulullah yang terdapat dalam buku “Agungnya Taman Cinta Sang Rasul”. Tujuan dilakukannya penelitian adalah untuk mengembangkan teks hadits terkait komunikasi kepada istri, bagaimana menghadapi kecemburuan seorang istri, terutama dalam keluarga poligami. Metode penelitian yang digunakan adalah kualitatif deskriptif dengan analisis wacana Teun A. van Dijk. Subjek dalam penelitian yaitu hadits dalam buku “Agungnya Taman Cinta Sang Rasul”, objek penelitannya adalah percakapan yang terdapat dalam hadits. Teknik pengumpulan data dilakukan dengan observasi teks, wawancara dan kajian pustaka. Hasilnya, dari segi teks, topik utamanya mengenai suatu perjalanan Rasulullah beserta beberapa istri dan sahabatnya. Di dalamnya menggambarkan kecemburuan Aisyah terhadap Shafiyyah, serta tanggapan Rasulullah yang memahami kondisi Aisyah dengan sabar dan menjelaskan dengan penuh kasih sayang. Bentuk kalimat dalam wacana tersebut adalah induktif (Rasulullah menjelaskan tentang kecemburuan di akhir), teks mengandung arti koheren (hubungan sebab akibat) satu sama lain. Terdapat kata ganti yang mengandung makna yang dalam dan bisa mempengaruhi suasana komunikasi. Menggunakan Bahasa dengan kontekstual yang formal (menceritakan terkait sunnah Rasul yang merupakan kisah ilmiah yang dijadikan referensi). Di akhir teks hadits, Rasulullah menggunakan kalimat kiasan sehingga memiliki nilai sastra dan sarat akan makna. Dari segi kognisi sosial, Aisyah merasa bahwa Rasulullah lebih mendahulukan Shafiyyah sehingga muncul rasa cemburu. Dari segi analisis sosial, beberapa di antara keluarga yang poligami masih belum mengimplementasikan komunikasi yang dicontohkan Rasulullah.